The Level Of Farmer Satisfaction With Field Agricultural Extension Services In The Passo Village Farmer Group, Baguala District, Ambon City - Paulany Walalayo; R. A. Far- Far; M. T. F Tuhumury (Cita konsultindo, 2023)
This study aims to analyze the level of farmer satisfaction with the performance of agricultural extension services in the Paso village farmer group. This research is a descriptive research. Data collection methods through interviews, observation and documentation. Sampling using the Simple random sampling method is randomly to farmers who are members of farmer groups as many as 31 respondents. Data analysis techniques for indicators of farmer satisfaction with agricultural extension services using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that the level of farmer satisfaction with the performance services of agricultural extension workers in Passo village based on IPA analysis illustrates that the dominant quadrant of agricultural extension performance attributes lies in quadrant II as many as eight (8) attributes, it shows that most of the attributes are in accordance with farmers' expectations, and farmer satisfaction with the overall performance of agricultural extension workers is categorized as very satisfied with a CSI value of 82.37.